2017
DOI: 10.5301/ijbm.5000311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance and utility of a NNMT-based urine test for bladder cancer

Abstract: Our data indicate that NNMT is a promising biomarker that could be used to support the early and noninvasive diagnosis of BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 39 publications
0
39
1
Order By: Relevance
“…High expression of NNMT has been reported in multiple cancer types . Several studies have shown that the elevated NNMT level in cancer can be used for the early diagnosis and noninvasive diagnosis of some malignant tumors . Interestingly, NNMT has been considered as a novel and sensitive serum biomarker for CRC detection, outperforming the clinical significance of carcinoembryonic antigen (CEA) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of NNMT has been reported in multiple cancer types . Several studies have shown that the elevated NNMT level in cancer can be used for the early diagnosis and noninvasive diagnosis of some malignant tumors . Interestingly, NNMT has been considered as a novel and sensitive serum biomarker for CRC detection, outperforming the clinical significance of carcinoembryonic antigen (CEA) .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Several studies have shown that the elevated NNMT level in cancer can be used for the early diagnosis and noninvasive diagnosis of some malignant tumors. [13][14][15] Interestingly, NNMT has been considered as a novel and sensitive serum biomarker for CRC detection, outperforming the clinical significance of carcinoembryonic antigen (CEA). 12 However, it was recently reported that NNMT was expressed in stroma and served as a major metabolic regulator of ovarian cancer-associated fibroblasts (CAF).…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with what reported by other studies, which explored NNMT expression in different solid tumours. Indeed, enzyme upregulation was described in a wide variety of neoplasms, including papillary thyroid carcinoma, stomach, colorectal and pancreatic cancer, ccRCC, OSCC, BC, NSCLC and lastly in melanoma …”
Section: Discussionmentioning
confidence: 99%
“…Enzyme overexpression was reported in numerous neoplasms, including clear cell renal cell carcinoma (ccRCC), oral squamous cell carcinoma (OSCC), non‐small cell lung cancer (NSCLC), bladder cancer (BC) and recently cutaneous and oral malignant melanoma …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation